Transformasi Pendidikan Era Kecerdasan Buatan: Simplifikasi Model UTAUT 2 dalam Evaluasi Penggunaan ChatGPT oleh Siswa SMA - Anindita Pratita; Tri Lathif Mardi Suryanto (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
. ChatGPT is one of the growing innovations in artificial intelligence (AI) technology in the field of education, aiming to assist humans in finding information and completing work efficiently. However, students' lack of understanding of the positive uses and benefits of ChatGPT as a self-learning medium results in low adoption rates and underutilized learning potential. Therefore, this study aims to understand the level of acceptance and the impact that influences students in adopting ChatGPT technology so that it can provide direction and recommendations for schools to increase their self-learning awareness through the utilization of AI. The study used a quantitative approach and interviews with public high school students with the construction of the UTAUT 2 model as a framework. The population of public high school students was 3,405, probability sampling was used as the sampling method then the data was processed using SEM analysis using SmartPLS 3.2.9 software.